2016
DOI: 10.1002/jhm.2599
|View full text |Cite
|
Sign up to set email alerts
|

Engaging hospitalists in antimicrobial stewardship: Lessons from a multihospital collaborative

Abstract: Inappropriate antimicrobial use in hospitalized patients contributes to antimicrobial‐resistant infections and complications. We sought to evaluate the impact, barriers, and facilitators of antimicrobial stewardship best practices in a diverse group of hospital medicine programs. This multihospital initiative included 1 community nonteaching hospital, 2 community teaching hospitals, and 2 academic medical centers participating in a collaborative with the Centers for Disease Control and Prevention and the Insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 12 publications
0
21
0
1
Order By: Relevance
“…Social barriers such as perception of resistance, mistrust in antibiotic guidelines, and the skepticism of antimicrobial stewardship importance also affect the application of ASPs. (6,11,15) Other studies reported that sociocultural beliefs, logistic barriers, and ethical concerns put impact in the implementation of ASPs (8,13).…”
Section: Social Barriers Logistic and Ethical Concernsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social barriers such as perception of resistance, mistrust in antibiotic guidelines, and the skepticism of antimicrobial stewardship importance also affect the application of ASPs. (6,11,15) Other studies reported that sociocultural beliefs, logistic barriers, and ethical concerns put impact in the implementation of ASPs (8,13).…”
Section: Social Barriers Logistic and Ethical Concernsmentioning
confidence: 99%
“…One of the significant prescribing barriers is hierarchical structures (6,11,17). The study reported that the hospital hierarchies and consultation etiquette result in conflict between several physicians.…”
Section: Hospital Hierarchiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sebagai contoh, belum tersedianya dokter atau apoteker yang memiliki spesialisasi infeksi tidak menjadi penghambat keberhasilan implementasi ASP seperti yang telah dibuktikan pada beberapa artikel penelitian. 66,72 Selain itu, kerjasama antarinstitusi dapat dilakukan untuk mengatasi keterbatasan dalam mengimplementasikan ASP, dan kerjasama tersebut tidak terbatas antarinstitusi kesehatan saja, tetapi juga dapat berupa kerjasama antara institusi kesehatan dan institusi pendidikan. 73 Proses identifikasi bentuk dan teknis kerjasama antarinstitusi perlu dilakukan agar implementasi ASP dapat memberikan manfaat bagi seluruh pihak yang terlibat dalam kerja sama.…”
Section: Upper-middle-income Economies (N) High-income Economies (N)unclassified
“…Hospitalists can likewise be vital partners in stewardship efforts, because their discipline is expanding rapidly, and they often are involved with quality improvement efforts and the efficient use of healthcare resources. A previous multisite hospitalist collaborative successfully enhanced antimicrobial documentation, accessibility to local guidelines, and implementation of a 72-hour antibiotic timeout [75]. The Vermont Oxford Network's Newborn Improvement Collaborative for Quality is an interdisciplinary association that has focused on antimicrobial stewardship for its 2016 and 2017 organization goals [76].…”
Section: Training Other Staff In Stewardship Effortsmentioning
confidence: 99%